Corticosterone impairs gap junctions in the prefrontal cortical and hippocampal astrocytes via different mechanisms. (15th March 2018) - Xia, Cong-Yuan; Wang, Zhen-Zhen; Zhang, Zhao; Chen, Jiao; Wang, Ying-Ying; Lou, Yu-Xia; Gao, Yan; Luo, Piao; Ren, Qian; Du, Guo-Hua; Chen, Nai-Hong
Abstract: Increasing evidence has implicated astrocyte pathology in the etiopathology of major depressive disorder (MDD). In particular, dysfunction of gap junctions in astrocytes is a potential target for MDD treatment. However, the mechanism underlying stress-induced dysfunction of gap junctions is still unknown. We therefore studied the mechanism of stress-induced dysfunction of gap junctions in prefrontal cortical and hippocampal astrocytes. Corticosterone (CORT) was used to induce stress conditions; CORT damaged the function of gap junctions, which resulted from less distribution of connexin43 (Cx43) on membranes and the enhanced phosphorylation of Cx43 at S368. Moreover, CORT downregulated the biosynthesis of Cx43 but increased the degradation of Cx43. Interestingly, both autophagy and the proteasome system were involved in the degradation of Cx43 in prefrontal cortical astrocytes, but only the proteasome system was involved in the degradation of Cx43 in hippocampal astrocytes. CORT significantly induced the formation of annular gap junction vesicles in prefrontal cortical astrocytes; however, Cx43 mainly presented as small dots in the hippocampal astrocytes. Furthermore, CORT increased N-Cadherin expression and the interactions of Cx43 with ZO-1/drebrin in prefrontal cortical astrocytes, but these interactions were oppositely modulated in hippocampal astrocytes. In conclusion, this study clarified the alternations of the Cx43 life cycle in the prefrontal cortical and hippocampal astrocytes exposed to CORT, which may contribute to our understanding of the mechanisms underlying stress-induced dysfunction of gap junctions. Highlights: Gap junction dysfunction in astrocytes is a potential target for MDD treatment. The mechanism of stress-induced dysfunction of gap junctions was studied. Corticosterone (CORT) was used to mimic aspects of stress conditions in astrocytes. CORT induced gap junctions dysfunction by regulating Cx43 life cycle.